Simulation of tensile fracture and strength prediction of high-lock titanium alloy bolt under eccentric load - FENG Derong; GUO Raolong; YU Weilin; LI Chao; LI Zhao; HUANG Zhangdong; XIA Jinqi; WAN Qiang (Jixie qiangdu, 2025)
The eccentric installation of high-lock titanium alloy bolts (an assembly angle between the bolt head and the fastening plate) leads to premature failure, which seriously affects the safe operation of aerospace aircraft. Currently, the test research is difficult to obtain the bolt fracture process, which in turn limits the revealing of fracture mechanism. Meanwhile, test research cannot obtain the fracture strength variation value of bolts with different assembly angles. Therefore, in response to the problem of premature fracture of high-lock bolts in the eccentric installation, finite element analysis method was employed and the model was verified by test. The verified finite element model was used to visualize the fracture process of eccentric installation bolts and predict the tensile strength of eccentric installation bolts with different angles. The research results indicate that the tensile strength and fracture position of bolts with installation angles of 0° and 3° obtained from finite element analysis are consistent with the test results, which show that the finite element model has good accuracy. As the installation angle increases, both the bolt head and thread are subjected to eccentric loads, and the bending moment generated aggravates the stress concentration in these two areas. When the assembly angle is less than 3°, the stress at the thread is larger, and when the angle is over 3°, the stress on the head is greater. The finite element model successfully predicts the tensile strength of bolts with an assembly angle of 1°, 2°, and 4°. The research results effectively reveal the fracture mechanism of high-lock titanium alloy bolts under the eccentric load. Meanwhile, the simulation model can predict the tensile strength of bolts under different installation angles, and provide technical specifications for the service of eccentric bolts.